2016
DOI: 10.1371/journal.pone.0147631
|View full text |Cite
|
Sign up to set email alerts
|

Zfrp8/PDCD2 Interacts with RpS2 Connecting Ribosome Maturation and Gene-Specific Translation

Abstract: Zfrp8/PDCD2 is a highly conserved protein essential for stem cell maintenance in both flies and mammals. It is also required in fast proliferating cells such as cancer cells. Our previous studies suggested that Zfrp8 functions in the formation of mRNP (mRNA ribonucleoprotein) complexes and also controls RNA of select Transposable Elements (TEs). Here we show that in Zfrp8/PDCD2 knock down (KD) ovaries, specific mRNAs and TE transcripts show increased nuclear accumulation. We also show that Zfrp8/PDCD2 interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…Mutually exclusive interactions of uS5 with ZNF277 and PRMT3 result in the formation of PDCD2-uS5-ZNF277 (lower left) and PDCD2L-uS5-ZNF277 (lower right) complexes. The existence of conserved complexes in Drosophila is supported by results from high-throughput two-hybrid screening and biochemical studies (28,30), showing that homologs of PRMT3 (Art3), ZNF277 (CG9890), PDCD2 (Zfrp8), and PDCD2L (Trus) interact with uS5 (Sop).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mutually exclusive interactions of uS5 with ZNF277 and PRMT3 result in the formation of PDCD2-uS5-ZNF277 (lower left) and PDCD2L-uS5-ZNF277 (lower right) complexes. The existence of conserved complexes in Drosophila is supported by results from high-throughput two-hybrid screening and biochemical studies (28,30), showing that homologs of PRMT3 (Art3), ZNF277 (CG9890), PDCD2 (Zfrp8), and PDCD2L (Trus) interact with uS5 (Sop).…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, biochemical analysis revealed that PDCD2 and PDCD2L form distinct complexes with uS5-PRMT3, because PDCD2L was not detected in a PDCD2 purification, and reciprocally, PDCD2 was not identified as a PDCD2L-associated protein (29). Interestingly, the uS5-PDCD2 interaction has been also observed in Drosophila (30).…”
mentioning
confidence: 99%
“…Tsr4 is evolutionarily conserved among eukaryotes (30). PDCD2/Zfrp8 in Drosophila directly interacts with Rps2, is both cytoplasmic and nuclear, and appears to serve a function in 40S production, but the significance of its interaction with Rps2 has not been extensively characterized (29,41,49). Humans have two Tsr4 homologs, PDCD2 and PDCD2L (30), and expression of human PDCD2 can fully complement the loss of Drosophila PDCD2/Zfrp8, indicating functional conservation (49).…”
Section: How Does Tsr4 Facilitate Rps2 Expression?mentioning
confidence: 99%
“…Based on data from sequence analyses, PDCD2 is thought to have arose from a duplication of the PDCD2L gene prior to the divergence of animals, fungi, and plants from a common ancestor (28). Interestingly, it was recently found that the Drosophila homolog of PDCD2, Zfrp8, interacts with Rps2 (52). Considering the seemingly similar functions ascribed to human PDCD2L and Drosophila PDCD2 (Zfrp8), we examined whether human PDCD2 contributes to ribosome biogenesis and potentially acts redundantly to PDCD2L.…”
Section: Fig 3 Pdcd2l Associates With Late 40s Precursors (A) Gfp-pdmentioning
confidence: 99%